2018
DOI: 10.1002/srin.201800305
|View full text |Cite
|
Sign up to set email alerts
|

Reformation Behavior of Austenite in 2205 Duplex Stainless Steel with Rapid Heat Treatment

Abstract: The reformation behavior of austenite in coarsened ferrite grains of 2205 duplex stainless steel is studied by means of rapid heat treatment process. With the prolongation of peak temperature holding time, ferrite grains coarsen significantly from 200 µm at 1 s to over 1000 µm at 10 min, and the reformation of grain boundary austenite is suppressed while fine equiaxed intragranular austenite is promoted during the subsequent isothermal treatment at 850 °C owing to the reduction of total ferrite grain boundary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Thus, nucleation of austenite is easier with a slow cooling rate (high arc energy and lower cooling rate). The increasing cooling time resulted in the appearance of intergranular austenite and Widmanstätten austenite (WA), which caused the higher measured austenite fraction [29]. Varbai et al concluded that the most decisive factor in the austenite/ferrite ratio in the HAZ is the applied thermal cycle since there was no significant nitrogen loss.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, nucleation of austenite is easier with a slow cooling rate (high arc energy and lower cooling rate). The increasing cooling time resulted in the appearance of intergranular austenite and Widmanstätten austenite (WA), which caused the higher measured austenite fraction [29]. Varbai et al concluded that the most decisive factor in the austenite/ferrite ratio in the HAZ is the applied thermal cycle since there was no significant nitrogen loss.…”
Section: Resultsmentioning
confidence: 99%